2019
DOI: 10.3389/fnins.2018.01005
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Based Attenuation Correction of PET/MRI in Pediatric Brain Tumor Patients: Evaluation in a Clinical Setting

Abstract: Aim: Positron emission tomography (PET) imaging is a useful tool for assisting in correct differentiation of tumor progression from reactive changes. O-(2-18F-fluoroethyl)-L-tyrosine (FET)-PET in combination with MRI can add valuable information for clinical decision making. Acquiring FET-PET/MRI simultaneously allows for a one-stop-shop that limits the need for a second sedation or anesthesia as with PET and MRI in sequence. PET/MRI is challenged by lack of a direct measure of photon attenuation. Accepted sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 40 publications
1
90
0
1
Order By: Relevance
“…Similarly, a deep convolutional neural network that derived attenuation maps based on ZTE images was shown to outperform both ZTE and atlas-based method in Blanc-Durand et al [43]. Interestingly, while most evaluations have been performed with adults with normal anatomy, Ladefoged et al [103] evaluated deep learning methods in pediatric brain tumor patients, with robust performance. The preliminary results obtained with these methods are encouraging.…”
Section: Methods Based On Atlas or Database Approaches Including Machmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a deep convolutional neural network that derived attenuation maps based on ZTE images was shown to outperform both ZTE and atlas-based method in Blanc-Durand et al [43]. Interestingly, while most evaluations have been performed with adults with normal anatomy, Ladefoged et al [103] evaluated deep learning methods in pediatric brain tumor patients, with robust performance. The preliminary results obtained with these methods are encouraging.…”
Section: Methods Based On Atlas or Database Approaches Including Machmentioning
confidence: 99%
“…In regard to novel applications, a recent study showed the benefit of PET/MR in low activity imaging (14 MBq) of [ 15 O]-H2O PET for quantitative relative cerebral blood flow (rCBF) assessment in unsedated healthy newborn infants [209]. In this regard, applying and modifying existing MRAC methods to pediatric cohorts such as in Ladefoged et al [103] are encouraged.…”
Section: Emerging Clinical and Research Applicationsmentioning
confidence: 99%
“…[19][20][21][22][23][24][25] DLMs have been primarily proposed for pCT generation from magnetic resonance imaging (MRI). [26][27][28][29][30][31] They are particularly appealing owing to their fast computation time. One of the first DLMs for pCT generation was based on the U-Net architecture.…”
Section: Introductionmentioning
confidence: 99%
“…The Deep-UTE method produces more robust clinical metrics using CT-AC and overall patient survival time is increased. PET/MRIs' attenuation correction in the Deep-UTE method is reliable for brain tumor evaluation due to better noise handling capability and less runtime properties [81].…”
Section: Brain Tumor Evaluationmentioning
confidence: 99%